Belt Mount Sets from the Shekshovo Medieval Burial Ground in the Suzdal Opolie - Irina E. Zaytseva (Археология евразийских степей)
The article deals with the metal parts of the belt set from the Shekshovo burial ground in the Suzdal Opolie (X–XII centuries). The objects originate mainly from the upper plowed layer. Most of them are related with destroyed burials, carried out by cremation rite: on the surface or in shallow pits. In total, about 200 finds were collected: solitary finds and 18 typological series of 2–39 items. Along with the significant predominance of finds of the second half of the X – beginning of the XI century, there are samples dated from other monuments of the IX – beginning of the X century and not found in complexes of later times. They are connected by their origin with the Saltovo antiquities. Probably, these finds mark the beginning of the use of the burial ground in the first half of the X century, although the greatest activity developed here in the middle of X–XII century.